1989
DOI: 10.1088/0022-3727/22/2/003
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the frequency dependence of ICP radiation noise

Abstract: Radiation noise power spectra were measured at frequencies from 20 Hz up to 3 kHz in high-frequency inductively coupled plasma (ICP). Aerosol sample radiation excess noise compared to that of argon radiation at frequencies of about 2 kHz and lower was observed. This excess noise is interpreted as a modulation of the radiation intensity by evaporating aerosol droplets. Further understanding and measurements of the noise spectra can be useful in both sample flow and droplet evaporation rate studies and analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…It follows that using eqn (28) and (31) is the most general solution for the computation of the standard deviation of LA-ICPMS data. Moreover, for years eqn (31) has been the only mathematical solution for the estimation of standard deviations in LA-ICPMS detection calculations.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…It follows that using eqn (28) and (31) is the most general solution for the computation of the standard deviation of LA-ICPMS data. Moreover, for years eqn (31) has been the only mathematical solution for the estimation of standard deviations in LA-ICPMS detection calculations.…”
Section: Datamentioning
confidence: 99%
“…13, 14 The net count number 1. THE √2NB RULE AND ITS SIZE [28] Principles of size evaluation; the √2Nb rule as an example. The most basic of all decision rules for paired measurements is the √2Nb rule (eqn (18)) and a generalisation of it suitable for unequal sample/background counting times:…”
Section: About the Poisson-gauss Approximation Of Confidence Intervalsmentioning
confidence: 99%
“…52,65 In the late 1980's, Antanavičius and co-workers studied ICP-AES signals for gaseous samples and aerosols obtained by solution nebulisation and injection of metal oxide powders in the ICP. [66][67][68] It was shown that the power spectral density of low frequency (icker) noise obtained for aerosols increases by an order of magnitude compared to gaseous samples. Similar data (for helium ICP) were obtained by Montaser and co-workers.…”
Section: Fluctuating M Sample Introduction Process?mentioning
confidence: 99%
“…In ICP-AES measurements, the attainable precision is influenced by both random (white) and time-correlated noise [4][5][6][7][8][9][10][11]. The most common white noise types are shot-noise and thermal noise, which can be minimized by using long integration times and cooled detectors, respectively.…”
Section: Introductionmentioning
confidence: 99%